Quantitative Trait Loci Associated with Seed Weight in Mungbean (Vigna radiata (L.) Wilczek) - Alam, A.K.M. Mahbubul; Somta, Prakit; Muktadir, M.A.; Srinives, Peerasak (Agriculture and Natural Resources, 2014)
Seed weight is an important yield component of pulse crops. In mungbean (Vigna radiata (L.) Wilczek), varieties with higher seed weight (larger seed size) are generally preferred for cultivation and consumption. Large seed size is thus a major target trait in mungbean breeding. This study considered quantitative trait loci (QTL) mapping in mungbean using a population of 142 F2:3 lines derived from a cross between BARImung 1 (low seed weight) and BARImung 6 (medium seed weight). The population was grown under field conditions in two locations in Bangladesh in 2012 and analyzed with 72 polymorphic simple sequence repeat markers. A single marker analysis suggested at least four loci controlling seed weight. Composite interval mapping consistently identified four QTL— qSWT1, qSWT6, qSWT8 and qSWT9— on linkage groups 1, 6, 8 and 9 in both locations. These QTL accounted for 5.80 to 19.96% and 8.31 to 33.72% of the seed weight variation depending on the location. qSWT1, qSWT8 and qSWT9 were common to QTL for seed weight detected previously in mungbean, while qSWT6 appears to be a new locus. qSWT1, qSWT6, qSWT8 and qSWT9 are conserved in other Vigna crops.